2011
DOI: 10.1021/ol2023505
|View full text |Cite
|
Sign up to set email alerts
|

Practical Radical Cyclizations with Arylboronic Acids and Trifluoroborates

Abstract: Practical radical cyclizations using organoboronic acids and trifluoroborates take place in water, open to air, and in a scalable fashion employing catalytic silver nitrate and stoichiometric potassium persulfate. Both Pschorr-type cyclizations and tandem radical cyclization/trap cascades are described, illustrating the utility of these mild conditions for the generation of polycyclic scaffolds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
86
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(87 citation statements)
references
References 56 publications
(28 reference statements)
1
86
0
Order By: Relevance
“…35 A year later, they demonstrated an intramolecular variant that could utilize either boronic acids or trifluoroborates (Figure 15). 36 Utilizing quinones as radicophiles, the Baran group were able to perform a radical/radical domino reaction to yield 100 . In this process, Ag(II) is generated via a persulfate-mediated single electron oxidation.…”
Section: Transition Metal-mediated Domino Reactionsmentioning
confidence: 99%
“…35 A year later, they demonstrated an intramolecular variant that could utilize either boronic acids or trifluoroborates (Figure 15). 36 Utilizing quinones as radicophiles, the Baran group were able to perform a radical/radical domino reaction to yield 100 . In this process, Ag(II) is generated via a persulfate-mediated single electron oxidation.…”
Section: Transition Metal-mediated Domino Reactionsmentioning
confidence: 99%
“…[4] Though it is a milder protocol, unfortunately the reaction is limited to only aliphatic nucleophiles. [8] In this context, the synthesis of such Het-Ar and Quin-Ar compounds by iron catalysis is desirable because of the environmental benignity, low cost, and availability of iron. [8] In this context, the synthesis of such Het-Ar and Quin-Ar compounds by iron catalysis is desirable because of the environmental benignity, low cost, and availability of iron.…”
Section: Introductionmentioning
confidence: 99%
“…Encouragement in this regard was found in the work of Sanford and Glorius, who had demonstrated that cooperative catalysis between transition metals and photoredox catalysts is indeed possible (1517). Potassium organotrifluoroborates were identified as promising partners in this new class of cross-couplings, as previous reports have documented their ability to function as carbon radical sources upon single-electron oxidation (18, 19). Furthermore, Akita and co-workers have used Ir[dFCF 3 ppy] 2 (bpy)PF 6 (dFCF 3 ppy = 2-(2,4-difluorophenyl)-5-(trifluoromethyl)pyridine; bpy = bipyridine) as a catalyst for the oxidation of activated potassium organotrifluoroborates, demonstrating the feasibility of their implementation in the proposed single-electron transmetalation manifold (20, 21).…”
mentioning
confidence: 99%